Exploring the best method of forecasting for short term electrical energy demand (a research on energy demand of trakya region in Turkey) - Güneş, Mesut (My University, 2009)
Tahmin yöntemleri, zaman serileri, elektrik enerjisi tüketimi, SPSS, Minitab, Matlab ÖZET KISA SÜRELİ ELEKTRİK ENERJİSİ İHTİYACI İCİN EN İYİ YÖNTEMİN BELİRLENMESİ (TRAKYA BÖLGESİ ENERJİ İHTİYACI ÜZERİNE BİR ÇALIŞMA) Bu çalışma belli bir bölgeye ait saatlik tutulmuş elektrik enerjisi tüketimine ilişkin veriler üzerine kurulu tahmin yöntemlerinin uygulanmalarını kapsamaktadır. Bu kapsamda öncelikle elektrik sistemleri ve tahmin yöntemleri üzerine bilgi verilerek mevcut durum ortaya konmuştur. Bölge olarak Türkiyenin Avrupa kıtasında kalan kesimi yani Trakya bölgesi amaç olarak ele alındı. Mevcut elektrik tüketim verilerinin saatlik tutulması ve 2005 yılının tamamı, 2006 ve 2007 yıllarının bazı ayları olmak üzere toplam 23 aylık büyük bir veri üzerinde çalışılmasından dolayı “Quantitative” sayısal tahmin yöntemleri daha tutarlı sonuç vermesi acısından kullanıldı. Bu bölgeye yönelik her bir ayın son gününü takip eden 12 saatlik elektrik enerji tüketimine ilişkin tahmin teknikleri geliştirildi ve elde edilen veriler ışığında en uygun modeller belirlendi. Elde edilen tahmin modelleri elektrik enerjisi verilerine uygulandı ve sonuçlar tartışıldı. Forecasting methods, time series, electrical power consumption, SPSS, Minitab, Matlab

EXPLORING THE BEST METHOD OF FORECASTING FOR SHORT TERM ELECTRICAL ENERGY DEMAND (A RESEARCH ON ENEGRY DEMAND OF TRAKYA REGION IN TURKEY) This study includes applications of forecasting models established on the data that contain the electrical power consumption of a specific region which are observed hourly. At the beginning of the research, basic information about the electrical power system and the forecasting methods are given and the situation is clarified. Trakya region in Turkey which is in European side of Turkey is selected as the target region. The data is composed of hourly observed electrical energy values for the whole year of 2005 and some months of 2006 and 2007 which is 23 months in total. Because the data is large enough and the aim of the research is to establish accurate forecasting models for short term forecasting, quantitative methods are used. For this region, forecasting methods are improved for the short term electrical energy consumption that is the next 12 hours of the last day of each months and the best fitted model is determined for each months. The best fitted models are applied to the data and the related results are discussed.
Keywords: Elektrik_Türkiye_Bölgeler; Mühendislik